1997
DOI: 10.1007/bf01192200
|View full text |Cite
|
Sign up to set email alerts
|

Tumour regression in non-small-cell lung cancer following neoadjuvant therapy. Histological assessment

Abstract: In the scope of a prospective multi-centre study after neoadjuvant combined chemotherapy (carboplatin, ifosfamide, etoposide, vindesine) and radiotherapy (45 Gy) 40 resection specimens of locally advanced non-small-cell lung cancer were analysed in order to establish reproducible pathological/anatomical results of tumour regression. Resection specimens of 28 squamous cell carcinomas and 12 adenocarcinomas were investigated using serial sections of the primary lesion. The mean age of the patients was 57 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(44 citation statements)
references
References 28 publications
0
44
0
Order By: Relevance
“…We confirmed that clinical and pathological responses were good indicators of survival after neoadjuvant chemotherapy in stage III-N2 NSCLC patients. As previously reported, 3,19 less than 10% of viable tumor cells after neoadjuvant chemotherapy is a relevant threshold to identify patients with good or poor clinical outcome. Since it represents a reliable prognostic marker, we recommend to evaluate and report the percentage of living cancer cells after neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 72%
“…We confirmed that clinical and pathological responses were good indicators of survival after neoadjuvant chemotherapy in stage III-N2 NSCLC patients. As previously reported, 3,19 less than 10% of viable tumor cells after neoadjuvant chemotherapy is a relevant threshold to identify patients with good or poor clinical outcome. Since it represents a reliable prognostic marker, we recommend to evaluate and report the percentage of living cancer cells after neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 72%
“…Only the primary tumors were analyzed. All hematoxylin- and eosin-stained resection specimens processed for the original sign-out were reviewed by two of the authors to determine the score, which was based on a 4-tiered scale as described by Junker et al (24,25). This system evaluates the proportion of viable tumor cells in relation to the degree of tumor necrosis and fibrosis.…”
Section: Methodsmentioning
confidence: 99%
“…As an independent reference for tumor response, we chose the histopathologic tumor regression score of the corresponding formalin-fixed and paraffin-embedded surgical specimens, as described by Junker et al (24,25). …”
mentioning
confidence: 99%
“…16,17 This analysis was performed by two independent staff pathologists who were blinded for all other clinical data (S.E.B. and H.P.D.).…”
Section: Histopathologic Response Classificationmentioning
confidence: 99%